Identification key to the mosquito (Diptera: Culicidae) larvae of the Tongatapu Island group, Kingdom of Tonga. Issue 1 (2nd January 2017) - Swan, T.; Galatowitsch, M. L.
ABSTRACT: An illustrated key is provided for the identification of third and fourth instar larvae of the nine mosquito species known to occur in the Tongatapu island group, Kingdom of Tonga. This includes five Aedes species: Ae. aegypti (Linnaeus, 1762), Ae. albopictus (Skuse, 1895), Ae. horrescens Edwards, 1935, Ae. tongae Edwards, 1926, and Ae. vexans nocturnus (Theobald, 1903) and four Culex species: Cx. quinquefasciatus Say, 1823, Cx. annulirostris Skuse, 1889, Cx. albinervis Edwards, 1929, and Cx. sitiens Wiedemann, 1828. The key includes illustrations of diagnostic features of both the third and fourth instar larvae (siphon, tufts, saddle, comb scales and anal gills). This will help workers correctly identify mosquito larvae in the Tongatapu island group, of which several species ( Ae. aegypti, Ae. albopictus, Cx. quinquefasciatus, Cx. annulirostris ) are medically important vectors of disease.